Variable reluctance synchronous machines in saturated mode - Hleli Hanene; Flah Aymen; Tounsi Souhir (Institute of Advanced Engineering and Science, 2021)
Electric vehicle seems largely based on electrical machines. Finding the best motor type seems be important for having more performances and a transport system robustness. In this work, we present an analytical model of the synchronous machine with variable reluctances in linear and saturated modes. The angular position of the rotor (θ) and the phase current (i) will beused as parameters. The analytical model of this machine will allow us to determinate its magnetic characteristics such inductors, magnetic flux and electromagnetic torque. The results obtained by the analytical model are compared with those obtained by the finite element method. So, basing on Matlab/Simulink tool and by working with finite element method, these results are depicted and the paper objective is illustrated.